SEJARAH PEMIKIRAN EKONOMI ISLAM PERIODE AWAL 450 H/1058 M - RAHMAT ZUBANDI THAHIR (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2021)
The variants and patterns of Islamic economic thought from Islamic scholars provide a roadmap for Islamic economic empowerment and development. The economic activities of the Islamic community should refer to the concept of Islamic economics that has been built by the mujtahids. The principles of Islamic economics globally have historical equivalents to be used as the basis for Islamic economics from upstream to downstream. Islamic society only needs the will to implement it in real life in everyday life